AUDIT TO VALIDATE PHYSICAL AMOUNTS OF INVENTORIES - Elizalde Marín, Letty Karina; Veloz Navarrete, Carlos Fernando; Haro Velasteguí, Fermín Andrés (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The main objective of this research was to carry out a theoretical study of inventories as a fundamental factor for cost control and develop a practical exercise of an audit applied to validate the physical quantities of inventories in a company. To achieve this objective, a documentary investigation was carried out in order to argue the state of the art of the subject to be addressed, exposing the theoretical considerations of the inventories according to the International Accounting Standards and the International Financial Reporting Standards, as well as the role the auditor plays the moment to proceed with the internal control. In addition, the procedures and tests applied during the physical taking of inventories by the auditor were detailed, exposing the work papers and the documentation of the audit work carried out during the observation of the physical taking. Finally, a case study was presented, where the procedures, audit tests and work papers necessary to audit the inventory account in the financial statements given at a given date are explained.